Litigation Transformation in Law Enforcement Effort in Indonesia During the Covid-19 Pandemic - Dian Ratu Ayu Uswatun Khasanah; Madiha Dzakiyyah Chairunnisa (LPPM Universitas Terbuka, 2021)
The Covid 19 pandemic has accelerated digitization in all aspects of life. As an effort to deal with its spread, the legal realm has also undergone a transformation. The implementation of remote litigations during the Covid-19 pandemic has begun to take effect in line with the government's appeal for Physical/ Social distance. The litigations used the support of the internet network or known as e-litigation. It is nothing new in the world because previously developed countries, such as the United States, have used this method beforehand. The implementation of e-litigation in Indonesia is certainly different from other developed countries that are technologically ready. The implementation of e-litigation is a development of the previously implemented e-court program. This study examined the ins and outs of virtual litigations during the pandemic with all the regulations that assist them. The research used normative and empirical juridical methods that provide explanations so that it can be used as an evaluation of implementation during the pandemic period and towards the new normal era. The secondary data were taken from the primary materials from the regulations that apply during the pandemic and the new normal era. In addition, the secondary materials used were also from journals, books, and other literacy sources. The results of this paper can be used as a reference for further research on the transformation of law enforcement that puts forward the modernization of technology and information in fulfilling justice and social welfare.